Comprehensive Review of Advances in Radiology and Imaging Technologies for Diagnostic and Therapeutic Medicine - Alhumireen, Mazen Jazi; Al.Enazi, Mariam Adal; Alotaibi, Areej Abed; Altharwi, Hajar Mohammad; Almutairi, Abdualziz Aziz; almuhanna, Maram hashim; Alhamad, Mazen Mohammed; Alyabsi, Sultan Awadh Humaidan; Alenazi, Yousif Zaid Awad; AlHagri, Mohammed Abdullah (Journal of Ecohumanism, 2024)
Radiology and imaging are some areas where rapid strides have been made, thus contributing to diagnostic and therapeutic medicine. The detection of a specific pathology or disease or therapeutic intervention has required high precision. Whether it is simple X-ray or computed tomography scans, ultra-modern functional MRI scans, molecular imaging, and more, radiology has been through lots of improvements to enhance clinicians’ ability to make more accurate clinical decisions. This review aims to discuss the role of radiology throughout the years and specify the contemporary usefulness of these methods, using diagnosis and therapy as key aspects. In addition, the review highlights certain issues related to implementing these technologies in practice, such as costs, availability, and staff education. We also evaluate how these novelties contribute to patient benefit today and in the future or can lay the foundation for individualized treatment.